Decision Making System for Visitor Satisfaction of Labuhanbatu Library Using K-Means Method - Martiwi Sitorus; Masrizal Masrizal; Rahma Muti’ah (JINAV: Journal of Information and Visualization, 2023)
The K-Means research technique is used in this study. By using Satisfaction Variables and visits to college libraries, this research was conducted at the Labuhanbatu library. Researchers used a sample of 35 visitors for this study, which were tested using the Rapidminer data processing application. Where the results of this study showed the results of 18 people were satisfied and 17 people were neutral. Where it is stated that most visitors are satisfied with library services.